906. Surgical Site Infections in Children with Beta-Lactam Allergy: A Matched Cohort Study. (31st December 2020) - Huang, Felicia Scaggs; Mangeot, Colleen; Sucharew, Heidi; Simon, Katherine; Courter, Joshua D; Risma, Kimberly; Schaffzin, Joshua K
Abstract: Background: Surgical site infections (SSIs) are a significant cause of morbidity and mortality. The administration of appropriate pre-operative antimicrobial prophylaxis (AMP) reduces SSI risk and beta-lactam antibiotics are considered the most effective agents. Studies in adult patients found increased SSI risk in patients with documented beta-lactam allergy (BLA) due to use of second line AMP agents. The SSI risk in BLA pediatric patients is not well-described. Methods: We conducted a retrospective matched cohort study of patients (1-19 years-old) who underwent a surgical procedure at a quaternary pediatric hospital during 2010-2017. Patients with documented BLA at the time of surgery were matched 1:1 to patients with no BLA by age at surgery, National Surgical Quality Improvement Program (NSQIP) category, surgical calendar year, and presence of complex chronic conditions (CCC). AMP by BLA status was considered appropriate if recommended by the 2013 American Society of Health-System Pharmacists (ASHP) guidelines, antibiotic class appropriate, or recommended by an infectious disease physician. McNemar's test was used to assess differences in SSI rates and antibiotic regimen appropriate for BLA status between BLA and no BLA groups. Results: Of the 11878 surgical procedures among 9781 patients during the study period, 1021(9%) of patients had a reported BLA and we matched 9 72 . SSI was rare in both groups and there was no significant difference in rates (18 (1.9%) in no BLA, 17 (1.8%) in BLA, p=1.0). BLA were more likely to receive an antibiotic regimen considered inappropriate for BLA status (22%) compared to no BLA (3%) with 89% receiving a beta-lactam-containing AMP regimen (p< 0.01). Conclusion: BLA was not associated with increased SSI risk in the pediatric patients studied. Interestingly, a significant proportion of children with a documented allergy received a beta-lactam for AMP. This suggests some providers recognize that allergy labels are inaccurate and may be comfortable administering beta-lactam AMP regardless of allergy status. Disclosures: All Authors : No reported disclosures